Somatostatin inhibits gastric acid secretion after gastric mucosal prostaglandin synthesis inhibition by indomethacin in man. Issue 11 (November 1985) - Mogard, M H; Maxwell, V; Kovacs, T; Van Deventer, G; Elashoff, J D; Yamada, T; Kauffman, G L; Walsh, J H
Abstract : The inhibitory effect of indomethacin, 200 + 200 mg administered per os over 24 hours, on the prostaglandin E2 generative capacity of gastric mucosal tissue was determined in healthy male volunteers. The effect of prostaglandin synthesis inhibition on somatostatin induced suppression of food-stimulated acid secretion was tested. Peptone meal stimulated acid secretion was quantified in five healthy volunteers by intragastric titration with and without indomethacin pretreatment. Somatostatin doses of 200, 400, and 800 pmol/kg/h each significantly inhibited the peptone stimulated acid output. Indomethacin treatment, resulting in 90% inhibition of prostaglandin E2 synthesis, did not affect glucose- or peptone-stimulated acid output or modify the inhibitory action of somatostatin. Clinically, acid inhibition by somatostatin has been used to treat bleeding peptic ulcers. Ulcer haemorrhage may be preceded by an excessive use of drugs that inhibit prostaglandin synthesis such as aspirin or other non-steroidal anti-inflammatory agents. Recent observations in the rat indicate that prostaglandins mediate the inhibitory action of somatostatin on gastric acid secretion. The present results suggest that prostaglandins are not required for inhibition of gastric acid secretion by somatostatin in man.